1993
DOI: 10.1177/000841749306000404
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perceptions of the Role and Effectiveness of Occupational Therapists in Schools

Abstract: Teachers' expectations from occupational therapists working with exceptional children in two Ontario public school boards were explored in this study. Information was obtained through a questionnaire distributed to all teachers (N = 143) who had worked with occupational therapists and personal interviews conducted with 10 of these teachers. Findings suggested that all teachers believed that there was an important role for occupational therapists in the school system. They defined this role as offering program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 11 publications
4
37
0
Order By: Relevance
“…The results of phase two of this study supported that OTSBC service is beneficial to students with fine motor difficulties, which are consistent with the findings of previous studies that have shown occupational therapy consultation is the preferred method of providing occupational therapy services in the school (Barnes &Turner, 2001;Dunn, 1990;Fairbairn & Knowles, 1993;Pollock & Stewart, 1998;Thress-Suchy et al, 1999). Factors that facilitate and/or hinder occupational performance changes of students with fine motor problems were identified.…”
Section: Discussionsupporting
confidence: 91%
“…The results of phase two of this study supported that OTSBC service is beneficial to students with fine motor difficulties, which are consistent with the findings of previous studies that have shown occupational therapy consultation is the preferred method of providing occupational therapy services in the school (Barnes &Turner, 2001;Dunn, 1990;Fairbairn & Knowles, 1993;Pollock & Stewart, 1998;Thress-Suchy et al, 1999). Factors that facilitate and/or hinder occupational performance changes of students with fine motor problems were identified.…”
Section: Discussionsupporting
confidence: 91%
“…The occupational therapist and teachers jointly presented an entire class activity that engaged fine-motor, sensory motor, and visual perceptual skills. The coteaching format is supported by research indicating that teachers would like occupational therapists to provide more demonstration and modeling of suggested therapy strategies (Fairbairn & Davidson, 1993). The occupational therapist and the Downloaded by ["Queen's University Libraries, Kingston"] at 00:42 03 January 2015 teacher alternated in presenting the activity to the students and supporting student performance once directions were given.…”
Section: Methodsmentioning
confidence: 99%
“…Although the goals of therapists providing services to schools must be linked to educational goals (Fairbairn & Davidson, 1993), environmental factors should be addressed in the therapy process (Canadian Association of Occupational Therapists. 199 1 : Law et al, 1996).…”
Section: Rehabilitation Therap Ymentioning
confidence: 99%